2011
DOI: 10.1007/7854_2011_189
|View full text |Cite
|
Sign up to set email alerts
|

Forward Genetic Approaches to Understanding Complex Behaviors

Abstract: Assigning function to genes has long been a focus of biomedical research.Even with complete knowledge of the genomic sequences of humans, mice and other experimental organisms, there is still much to be learned about gene function and control. Ablation or overexpression of single genes using knockout or transgenic technologies has provided functional annotation for many genes, but these technologies do not capture the extensive genetic variation present in existing experimental mouse populations. Researchers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 189 publications
(174 reference statements)
0
6
0
Order By: Relevance
“…Similarly, involvement of some genes such as MsLFY [10], CONSTANS-LIKE [11], SPL13 [12], MsZFN [13], MsFRI-L [14], and MsFRI-L in alfalfa flowering time variation have been described using the reverse genetics approaches like molecular cloning and gene expression. However, single gene expression analysis with knockouts or transgenics seems insufficient to account for the extensive quantitative variation in the population [15], which can be explained using QTL mapping with a high-resolution genetic map.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, involvement of some genes such as MsLFY [10], CONSTANS-LIKE [11], SPL13 [12], MsZFN [13], MsFRI-L [14], and MsFRI-L in alfalfa flowering time variation have been described using the reverse genetics approaches like molecular cloning and gene expression. However, single gene expression analysis with knockouts or transgenics seems insufficient to account for the extensive quantitative variation in the population [15], which can be explained using QTL mapping with a high-resolution genetic map.…”
Section: Introductionmentioning
confidence: 99%
“…Phenotype-based or “forward genetics” approaches begin with the targeted behavioral phenotype (trait) and then involve subsequent genetic analysis of the trait. Most genetic studies of sensorimotor gating have focused on genebased approaches, and as such, these approaches are discussed in more detail than phenotype-based approaches, which are discussed more extensively in Tarantino and Eisener-Doman (2011). The goals for any genetic approach can be very different— some approaches seek to understand the more global role of a specific gene in a particular phenotype related to a disease, while others may be designed to elucidate the role of a particular gene in a cellular process, in neural circuit abnormalities, or in brain development.…”
Section: Approaches To Genetic Models Of Sensorimotor Gatingmentioning
confidence: 99%
“…ENU mutagenesis; (Tarantino and Bucan 2000) and quantitative trait loci (QTL) studies on crosses of inbred mouse strains with distinct phenotypes or on mice or rats selectively bred for PPI levels (Hitzemann et al 2008; Tarantino and Eisener-Doman 2011). Thus far, most of the PPI mutants identified through ENU mutagenesis screens have had some amount of hearing loss, and thus the specificity of the PPI “phenotype” was most likely confounded by deafness (Lisa Tarantino, personal communication).…”
Section: Approaches To Genetic Models Of Sensorimotor Gatingmentioning
confidence: 99%
“…The studies discussed so far were conducted in C57BL/6 mice but genotype affects phenotype (Logue, Owen, Rasmussen, and Wehner, 1997; Owen, Logue, Rasmussen, and Wehner, 1997; Tarantino and Eisener-Dorman, 2012; Tarantino, Gould, Druhan, and Bucan, 2000). In an examination of the effects of acute, chronic, and withdrawal from chronic nicotine on hippocampus-dependent learning in 8 different inbred strains of mice, it was found that genetic background differentially affected the acute and withdrawal effects of nicotine on hippocampus dependent learning (Portugal et al, 2012a).…”
Section: 0 Genetic Influencesmentioning
confidence: 99%